Combining two-directional synthesis and tandem reactions. Part 21: Exploitation of a dimeric macrocycle for chain terminus differentiation and synthesis of an sp3-rich library. Issue 11 (1st June 2015) - Storr, Thomas E.; Cully, Sarah J.; Rawling, Michael J.; Lewis, William; Hamza, Daniel; Jones, Geraint; Stockman, Robert A.
Graphical abstract: Abstract: The application of a tandem condensation/cyclisation/[3+2]-cycloaddition/elimination reaction gives an sp 3 -rich tricyclic pyrazoline scaffold with two ethyl esters in a single step from a simple linear starting material. The successive hydrolysis and cyclisation (with Boc anhydride) of these 3-dimensional architectures, generates unprecedented 16-membered macrocyclic bisanhydrides (characterised by XRD). Selective amidations could then be achieved by ring opening with a primary amine followed by HATU-promoted amide coupling to yield an sp 3 -rich natural product-like library.